A Atividdade de extensão na Universidade Estadual DE Goiás: perspectivas e ações, 2010 a 2017 - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The study focuses on the development and implementation of higher education in Brazil, especially the State University of Goiás (UEG); The mission of the University under the extension analysis. It aims to address the role of Extension Nuclei in Territorial Development (NEDETs) in support of the Rural Territories constituted by the Ministry of Agrarian Development (MDA). The actions developed with the interconnection between the extension practices carried out by the UEG and the Rural Territory of Southwest Goiania. The support to family farmers, which are of fundamental importance for productive and income generating, thus justifying the relevance of university and community partnership. The NEDET implementation project allows direct action in the territories, in order to train and qualify agents to promote sustainable rural development. We will base our research in Carvalho (2014), Oliven (2002), Santos (2014), Sampaio (1991), Ribeiro (1998), Peres , And Map of Higher Education (2015). The questions that discuss the regional context and the late establishment of higher education in Goiás are based on the works of Castro (1989), Sectec (2015) and Neves (2001), the questions regarding the trajectory of extension, with Morais (1996) , Bergia (1972), Piaget (1972), Gyamarti (1986), and Marco (1998), Serrano (2001), Freire (2015), Jezine (2004), Gramsci (2002), Casto and Júlia (1994), Barr (1998), Melo Neto (2003), Cabral Neto (2004), Lima Souza (2001), Serrano (2001) and Lucchesi (2002). The aim of this research is to present the courses of Brazilian higher education and its contemporary activities through the extension actions developed by the UEG and the Rural Territory of the Southwest
Keywords: Universidade; Extensão universitária; Extensão universitária - NEDET; Territórios Rurais; Extensão universitária - Territórios Rurais - UEG.; University; University Extension; University Extension - NEDET; Rural Territories; University Extension - Rural Territories - UEG; GEOGRAFIA REGIONAL::REGIONALIZACAO; GEOGRAFIA HUMANA::GEOGRAFIA AGRARIA